Neapolitan discourse in the narrative diary Mistero Napoletano (Altre Modernità, 2024)
Referring to ‘Discourse on the Cape of Good Hope’ by John Maxwell Coetzee, the definition ‘Neapolitan Discourse’ refers to the city of Naples and its socio-cultural environment, on one hand, and to certain themes and authors of Neapolitan Literature, on the other. Towards this Literature the position taken by the author is as much one of comparison as of confrontation. Firstly, I analyse the question about the existence of a proper Neapolitan Literature and its circumscription on the criterion of Neapolitanness. I define Neapolitan Literature as a literary production in which the author’s response to Neapolitanness as a whole becomes relevant (‘Neapolitan Discourse’). Secondly, the themes and authors addressed in Mistero napoletano will be circumscribed for the definiton of its ‘Neapolitan Discourse’. Specifically, the absence of dialect and linguistic mix between Italian and Neapolitan will be discussed, while Anna Maria Ortese and Raffaele La Capria will be identified as writers considered by Rea for his ‘Neapolitan Discourse’. Finally, I will discuss how Rea’s ‘Neapolitan Discourse’ can be seen as of interest to both a local and a national reader of Italian.
Keywords: Ermanno Rea; Mistero napoletano; Neapolitan literature; Neaples; diary